Indonesian Government Financial Auditing: A Bibliometric Analysis - Oktaviyani, Tri; Cris Kuntadi (Dinasti Publisher, 2023)
Examining the problem of government financial auditing from various past studies will be able to open up new opportunities to find more varied research and to get the renewal of a study, it is necessary to analyze previous research by mapping related research in the field of government financial auditing. This study aims to conduct mapping related to research in the field of government financial auditing in Indonesia published in various Scopus-indexed international journals. This type of research is desk research. The bibliometric analysis method was used in this research. It was found that research on Indonesian government financial audits has emerged since 2011. The total number of articles that discussed the topic and analyzed in this study was 91 articles. The year 2020 was the peak where articles were produced that year with the highest total of 18 articles. Aswar K., Erlina, and Setyaningrum D. were the most productive researchers and the University of Indonesia produced the most articles on the topic of auditing Indonesian government finances in the Scopus journal database. The subject areas with the most publications are Business, Management, and Accounting. Meanwhile, the most cited publication is Transparency of local government in Indonesia. Based on the results of this study, it can be concluded that research on government financial audits in Indonesia is increasing every year and is interesting for further research.